Analisis Implementasi Prosedur Profiling Bagasi Penumpang sebagai Instrumen Mitigasi Risiko Keamanan Penerbangan - Abdulhafizh Karnaen, Irfan; Mandrawaty, Vidyana; Yasmudi (Jurnal Manajemen Dirgantara, 2025)
Aviation security research is a top priority in air transportation operations. The purpose of this study is to analyze the passenger baggage profiling process for safety and comfort, including the inspection and documentation of baggage contents during check-in. However, various obstacles remain in the field, such as a lack of accuracy among officers, limited human resources, and equipment failures that can impact the smoothness and effectiveness of this process. The method used in this study is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation conducted during February to March 2025. Data analysis was carried out through the stages of data collection, data reduction and data presentation. The study results indicate that the profiling procedure has been carried out according to operational standards, but obstacles remain. Some of the main problems identified include a lack of attention to baggage conditions, passenger objections to the paid baggage policy, label printing machine problems, and a lack of personnel during peak operating hours. Solutions offered include routine officer training, increased passenger education, routine equipment inspections, and additional manpower to support the smooth running of the profiling process and maintain aviation safety standards.